ORTHODONTIC APPROACH IN THERAPY OF PATIENTS WITH DIABETES MELLITUS - Ichkova, Vanja; Grujoska Dimovska, Emilija; Bogdanovska, Biljana; Adamova, Katerina (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
We live in a modern society where a beautiful smile becomes commonplace, so orthodontic patients are not just children and teenagers but also adults. If we take into account that the age limit of patients is growing, the number of diseases that they may have is growing at the same time. Knowing that factors such as stress, overweight, and low physical activity are common causes for the development of diabetes mellitus, it is expected that diabetes would increase systemic diseases faced by dentists during orthodontic procedures. Diabetes mellitus is one of the most common chronic diseases whose number is constantly rising and is characterized by increased blood sugar concentration - hyperglycemia. Patients with diabetes mellitus who need orthodontic treatment require special treatment and knowledge of the changes that this disease gives in the oral cavity, periodontal changes in the supporting apparatus of the tooth, the tendency to infection, and the orthodontic tooth movements. In this review, we focus on the impact of diabetes on the oral changes, tooth movements, and considerations that every orthodontist needs to have when treating these patients. Keywords:  Orthodontic approach, Orthodontic treatment, Diabetes mellitus, Orthodontic tooth movement. https://doi.org/10.55302/JMS2251187i